2009
DOI: 10.1007/s11661-009-9870-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermokinetic Modeling of Phase Transformation in the Laser Powder Deposition Process

Abstract: A finite element model coupled with a thermokinetic model is developed to predict the phase transformation of the laser deposition of AISI 4140 on a substrate with the same material. Four different deposition patterns, long-bead, short-bead, spiral-in, and spiral-out, are used to cover a similar area. Using a finite element model, the temperature history of the laser powder deposition (LPD) process is determined. The martensite transformation as well as martensite tempering is considered to calculate the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Thus, the martensite phase is predominant near the interface as a result of the non-equilibrium phase transformation from austenite to martensite due to the rapid cooling rate. This diffusionless transformation of austenite arises only when the cooling rate is high enough to avoid diffusion of carbon atoms [ 28 , 45 , 65 ]. However, the cooling rate becomes lower as the number of newly-added layers increases and the heat inside the part is continuously accumulated, which subsequently causes the tempered martensite on the preceding layers [ 2 , 28 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the martensite phase is predominant near the interface as a result of the non-equilibrium phase transformation from austenite to martensite due to the rapid cooling rate. This diffusionless transformation of austenite arises only when the cooling rate is high enough to avoid diffusion of carbon atoms [ 28 , 45 , 65 ]. However, the cooling rate becomes lower as the number of newly-added layers increases and the heat inside the part is continuously accumulated, which subsequently causes the tempered martensite on the preceding layers [ 2 , 28 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, some studies of AISI 4140 alloy steel processed by LENS have been conducted to investigate its microstructure and mechanical properties [ 27 , 28 ]. However, only a limited number of investigations on LENS-based direct joining between metallic powder and corresponding wrought substrate have been carried out so far and, additionally, they were primarily limited to nickel-based Inconel 718 [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have shown previously for carbon steel that the deposition pattern can change the final properties of the deposited material significantly. [14] The deposition pattern defines the temperature history of the deposited material and, consequently, affects the phase transformation kinetics of the material. In this article, laser deposition of a hot-work tool steel, AISI H13, with approximately 9 pct alloy elements (0.35 pct C, 5.2 pct Cr, 1.3 pct Mo, 1.0 pct Si, and 1.0 pct V) is modeled.…”
Section: Introductionmentioning
confidence: 99%
“…Tempering the martensite has four steps: generating transition carbides (373 K to 523 K (100°C to 250°C)); transforming retained austenite to ferrite and cementite (473 K to 573 K (200°C to 300°C)); replacing the transition carbides with cementite and ferrite (starting from 523 K to 623 K (250°C to 350°C)); and forming alloy carbides in the temperature range of 773 K to 923 K (500°C to 650°C) for the materials containing a considerable amount of alloy elements such as chromium, titanium, tungsten, molybdenum, and vanadium. The alloy carbides in AISI H13 consist of [14] : M 6 C (containing principally molybdenum), M 7 C 3 (containing principally chromium), and MC (containing principally vanadium). Alloy carbides have more stability at high temperatures than cementite and maintain or even increase the hardness of the material at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Different aspects of this process, such as the feasibility to make near-net-shape parts [1,2], process planning and controlling [3,4], thermo-mechanical modeling, [5,6] and thermo-kinetic modeling [7] of the process have been investigated by a number of researchers. The quality of the process with the aid of real time monitoring and process control can be improved.…”
Section: Introductionmentioning
confidence: 99%